Seasonal changes in the prevalence ofHaemonchus andTrichostrongylus hypobiotic larvae in tracer goats in Malaysia - Ikeme, M. M.; Iskander, Fatimah; Chong, Lee Chu (Springer, 1987)
An investigation into the seasonal changes in the population structure of Haemonchus and Trichostrongylus in tracer goats was conducted over 12 months at Serdang, an area in southern West Malaysia with year-round tropical rainfall. Successive groups of parasite-free tracer goats were grazed for a month alongside naturally infected adult goats and necropsied for worm counts 14 days after their removal from pasture. No hypobiotic larvae of Trichostrongylus were recovered. Hypobiotic larvae of Haemonchus were evident during each month of the year but accounted for only a very small proportion of the total Haemonchus burden. Very low levels were encountered from December through to June. Comparatively higher levels of hypobiosis were observed thereafter with a peak of 7.4% in September. The factors responsible for hypobiosis were not clearly defined but the phenomenon was associated with increasing levels of soil moisture storage. Host resistance, adult worm population of tracers and population of ingested L3 were ruled out as possible inducing factors.